Natural Killer Cells in the Malignant Niche of Multiple Myeloma - Venglar, Ondrej; Bago, Julio Rodriguez; Motais, Benjamin; Hajek, Roman; Jelinek, Tomas (Frontiers in immunology, 2021)
Natural killer (NK) cells represent a subset of CD3- CD7+ CD56+/dim lymphocytes with cytotoxic and suppressor activity against virus-infected cells and cancer cells. The overall potential of NK cells has brought them to the spotlight of targeted immunotherapy in solid and hematological malignancies, including multiple myeloma (MM). Nonetheless, NK cells are subjected to a variety of cancer defense mechanisms, leading to impaired maturation, chemotaxis, target recognition, and killing. This review aims to summarize the available and most current knowledge about cancer-related impairment of NK cell function occurring in MM.
Keywords: Molecular Targeted Therapy; Tumor Microenvironment; Disease Management; Immunity; nádorové mikroprostředí; immunotherapy; Multiple Myeloma; Killer Cells, Natural; Prognosis; receptory buněk NK; výsledek terapie; náchylnost k nemoci; Cytotoxicity, Immunologic; imunita; imunomodulace; management nemoci; Immunomodulation; microenvironment; mnohočetný myelom; NK cells; prognóza; zvířata; Humans; biologické markery; inhibitory receptors; Disease Susceptibility; niche; multiple myeloma; cílená molekulární terapie; Receptors, Natural Killer Cell; T-Lymphocyte Subsets; Biomarkers; buňky NK; activating receptors; T-lymfocyty - podskupiny; Treatment Outcome; cytotoxicita imunologická; lidé; Animals